Evaluasi Peran Pendidikan Dasar dalam Konteks Sosial Masyarakat: Tinjauan Sosiologis - Elliza Nofri; Detri; Syofiani; Rieke Alyusfitri (STKIP Subang, 2026)
Basic education plays a strategic role not only in developing students’ academic competencies but also in shaping social awareness and character as members of society. This article aims to evaluate the role of basic education within the social context of society from a sociological perspective. A qualitative descriptive approach was employed through a literature review of scholarly sources related to the sociology of education and basic education. The analysis focused on examining the function of basic education as a social institution, an agent of socialization, and a medium for internalizing social values and norms. The findings indicate that basic education has a significant role in fostering social values, strengthening social integration, and preparing students to adapt to the dynamics of social life. However, this role has not been fully optimized due to various social factors, including diverse family backgrounds, community environments, and limited collaboration between schools, parents, and society. Therefore, strengthening the implementation of sociological foundations in basic education practices is essential to ensure that educational processes are more contextual, inclusive, and responsive to social realities. This study is expected to provide a conceptual contribution to the development of policies and practices in basic education oriented toward enhancing students’ social competencies